THE INFLUENCE OF PRODUCT KNOWLEDGE, PRODUCT EXPERIENCE, AND PRODUCTS BENEFITS ON CUSTOMERS’ SATISFACTION AND ITS IMPACT ON E-WOM MS GLOW COSMETIC CUSTOMERS IN PALU CITY - Nur Faizan, Safna; Dg. Parani, Syamsul Bahri; Tombolotutu, Muzakir (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims to determine and analyze the influence of product knowledge, product experience and product benefits have significant effect on customers’ satisfaction and its impact on the E-Wom of MS Glow Cosmetics customers in Palu City. The research population were MS Glow Cosmetics customers in Palu City. The sample in this research were 80 respondents. This is causal descriptive research with the data analysis technique used is partial least square (PLS). The data analysis technique used a smart software program (PLS) 3.0. The results reveal that the product knowledge variable have positive and significant influence on customers’ satisfaction with MS Glow Cosmetics in Palu City with a Sig-t value of 0.003. Furthermore, the product knowledge variable has positive and significant influence on the E-Wom of MS Glow Cosmetic customers in Palu City with a Sig-t value of 0.002. The product experience variable has positive and significant influence on customer satisfaction with MS Glow Cosmetics in Palu City with a Sig-t value of 0.000. The product experience variable has an influence, but is not significant on the E-WOM of MS Glow Cosmetics customers in Palu City with a Sig-t value of 0.176. Furthermore, the product benefit variable has an influence, but is not significant on customer satisfaction with MS Glow Cosmetics in Palu City with a Sig-t value of 0.095. The product benefit variable has a positive and significant influence on the E-Wom of MS Glow Cosmetics customers in Palu City with a Sig-t value of 0.049. And finally, the customer satisfaction variable has a positive and significant influence on the E-WOM of MS Glow Cosmetics customers in Palu City with a Sig-t value of 0.010. Keywords : Product Knowledge, Product Experience, Product Benefits, Customer Satisfaction and E-Wom.